Using Social Network Analysis to explore Learning networks in MOOCs discussion forums - Soleymani, Ali; Itard, Laure; de Laat, Maarten; Valle Torre, Manuel; Specht, Marcus (CLIMA 2022 conference, 2022)
Learning and educational challenges in the field of indoor climate and building services like energy systems are mainly due to the transformation of professional practices and learning networks, a big shift in the way in which people work, communicate, and share their knowledge and the need for additional workforce, either juniors or coming from other disciplines. One of the most important factors that highly influence professional development and workplace learning is networked learning. Our goal in this study, is understanding the learning networks characteristics and patterns of interaction using Social Network Analysis techniques in three MOOCs discussion forums. The result of this study shows not only the importance of Learning networks and peer support on professionalization of learners, but also how pedagogical approach of instructors in MOOCs can foster learning networks. This novel approach in developing learning networks and communities is not only able to help connect young professionals and experienced practitioners digitally, but also it can promote professional development and innovation in the energy installation sector.